2022
DOI: 10.1002/ange.202208475
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecular‐Weight Additives Modulate Calcification by Interacting with Prenucleation Clusters on the Molecular Level**

Abstract: Small-molecular-weight (MW) additives can strongly impact amorphous calcium carbonate (ACC), playing an elusive role in biogenic, geologic, and industrial calcification. Here, we present molecular mechanisms by which these additives regulate stability and composition of both CaCO 3 solutions and solid ACC. Potent antiscalants inhibit ACC precipitation by interacting with prenucleation clusters (PNCs); they specifically trigger and integrate into PNCs or feed PNC growth actively. Only PNC-interacting additives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Moreover, beside our work, various papers from the literature have reported the tendency of calcium phosphate clusters to aggregate with time into branched structures. ,, These ramified networks of aggregated clusters are proposed to be the intermediate stage between individual PNS and solid ACP. , Hence, this transition would proceed by successive dehydration, driving PNS aggregation and then amorphous solid nucleation. It is worth noting that a similar process is proposed for CaCO 3 precipitation , even if branched aggregated clusters for the CaCO 3 system are not easily observed by electronic microscopy except in the presence of some organic additives that stabilize CaCO 3 PNS aggregates . However, computation studies have shown that ionic aggregates can be thermodynamically stable under the form of DOLLOP (dynamically ordered liquid-like oxyanion polymer) and that calcium carbonate PNS can be the individual building block of amorphous calcium carbonate ACC .…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, beside our work, various papers from the literature have reported the tendency of calcium phosphate clusters to aggregate with time into branched structures. ,, These ramified networks of aggregated clusters are proposed to be the intermediate stage between individual PNS and solid ACP. , Hence, this transition would proceed by successive dehydration, driving PNS aggregation and then amorphous solid nucleation. It is worth noting that a similar process is proposed for CaCO 3 precipitation , even if branched aggregated clusters for the CaCO 3 system are not easily observed by electronic microscopy except in the presence of some organic additives that stabilize CaCO 3 PNS aggregates . However, computation studies have shown that ionic aggregates can be thermodynamically stable under the form of DOLLOP (dynamically ordered liquid-like oxyanion polymer) and that calcium carbonate PNS can be the individual building block of amorphous calcium carbonate ACC .…”
Section: Discussionmentioning
confidence: 76%
“… Snapshots of CIT and HEDP in an aqueous CaCO 3 solution [155] . CIT, citrate; HEDP, bisphosphonate etidronic acid.…”
Section: Simulations Of Caco3 Nucleation With the Influence Of Inhibi...mentioning
confidence: 99%
“…With continuous binding of Ca 2+ to inhibitors, fewer ions are involved in PNCs formation and the nucleation process is therefore retarded. Duchstein et al [155] . described the dynamic interaction modes of citrate (CIT) and bisphosphonate etidronic acid (HEDP) with PNCs as shown in Figure 3.…”
Section: Simulations Of Caco3 Nucleation With the Influence Of Inhibi...mentioning
confidence: 99%